Anthropometric characteristics of brazilian young swimmers in different competitive categorie - Antonio Carlos Dourado; João Bartolomeu Neto; Christiano Bertoldo Urtado; Felipe Fedrizzi Donatto; Gerson dos Santos Leite; Richard Diego Leite; Jonato Prestes (Universidade Federal de Santa Catarina, 2006)
The objective of this study was to establish the profi le as well as the differences in anthropometric characteristics of Brazilian young swimmers of different categories in both sexes. Ninety male and 70 female swimmers were measured in the following categories: 1 (12-13 years), 2 (14-15 years) and 3 (16-18 years). Anthropometric variables analyzed were: body mass (Kg), stature (m), BMI (Kg/m2), fat free mass (LBM, kg), fat mass (kg) and arm span (m). The percent of body fat (% fat) was estimated using the Lohman equation. Two-way ANOVA was used followed by the Tukey's post-hoc test, with p< 0.05. For males, the category 3 presented higher body mass, stature, arm span and LBM in relation to the other categories. For females, body mass was higher in category 3 when compared to categories 1 and 2. It was observed higher stature, arm span, LBM and fat mass for category 3 when compared to 1. Category 2 presented higher body mass and LBM than category 1. Comparing to girls, boys in the category 2 had higher BMI and LBM than girls. For both categories 2 and 3, males showed higher body mass, stature, arm span and LBM than females, which, in turn, had higher % fat. It was concluded that anthropometric variables are different between categories for both sexes, however, among girls differences between categories 1 and 2 were less evident, probably because of early maturation changes in females. RESUMO O objetivo deste estudo foi verifi car o perfi l e as diferenças nas características antropométricas de jovens nadadores brasileiros, de distintas categorias, em ambos os gêneros. Foram avaliados 90 nadadores do sexo masculino e 70 do sexo feminino das categorias Infantil (12-13 anos), juvenil (14-15 anos) e junior (16-18 anos). As variáveis antropométricas mensuradas foram: massa corporal (Kg), estatura (m), IMC (Kg/m2), massa magra (kg), massa gorda (kg) e envergadura (m). O percentual de gordura (%G) foi obtido através da equação de Lohman. Na estatística, foi utilizado o teste Anova two way seguido de post hoc Tukey, com p<0,05. No gênero masculino, a categoria junior apresentou maior massa corporal, estatura, envergadura e massa magra em relação aos grupos infantil e juvenil. Para o gênero feminino, a massa corporal foi superior na categoria junior comparada à infantil e a juvenil. Foram observadas estatura, envergadura, massa magra e massa gorda maiores na categoria junior, quando comparadas à infantil. No sexo feminino, a categoria juvenil apresentou maior massa corporal e massa magra em relação ao grupo infantil. Na categoria infantil, os meninos apresentaram maior massa corporal e massa magra em relação às meninas. Na categoria juvenil, o masculino teve maior massa corporal, estatura, envergadura e massa magra em relação ao feminino, que teve maior %G. Na categoria junior, os meninos apresentaram maior massa corporal, estatura, envergadura e massa magra em relação às meninas, que apresentaram maior %G. Conclui-se que, existem diferenças nas variáveis antropométricas entre as categorias, em ambos os gêneros, entretanto, para o grupo feminino as diferenças antropométricas entre as categorias infantil e juvenil são menos evidentes, provavelmente, devido às alterações orgânicas e hormonais que ocorrem prematuramente em meninas.